Implications of the Digital Age on Social Engagement and Political Participation in the Context of Civic Education - Afandi, Afandi; Amanda, Dea; Laia, Della Anggriani; Billah, Syarifah Zulfa Aripah; Fatoni, Ummi; Virnanda, Virga (CV. Rayyan Dwi Bharata, 2023)
Digital technology plays a role in human life. It is important to understand how young people respond to and engage in political discussions on social media. Citizenship education is one of the efforts to deal with the implications of the digital era in order to form a young generation who has ethics and a responsible attitude in political participation. Therefore, this research will discuss in more depth the implications of the digital era for social and political involvement in civic education. This study uses a qualitative approach, while to obtain data, research uses literacy studies to obtain information regarding the implications of the digital era on social and political engagement. This research obtains the results of the implications of the digital era on social and political involvement in citizenship education that must be understood by the community, especially for individuals and groups who are in the world of politics. The digital age provides both opportunities and challenges for participatory social and political engagement. Therefore, civics education must be adapted and use approaches that are relevant to the digital era.